(untitled) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2024)
This work details the lighting intervention through the video mapping technique in nine self-built vernacular buildings in the region of Aysén, Chile. This exercise shows the importance of the visual arts as an indispensable resource and as a useful tool for the analysis of the different problems of the past, and its results tend to generate a new moment of cultural appropriation by its inhabitants and surrounding communities, and a greater recognition by the governmental public institution, the academy and the international community.